Pergulatan Perumusan Bermazhab secara Qawlī dan Manhajī dalam Baḥth al-Masā’il pada Muktamar Nahdlatul Ulama Ke-33 - Achmad Kemal Riza (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2018)
Baḥth al-masā’il is a forum in which traditionalist Muslims of Nahdlatul Ulama get their fatwas. Nahdlatul Ulama practices taqlīd and therefore madhhab in its fatwa by relying upon opinions of especially Shāfi‘ī jurists. Since 1992, some forward-minded people within Nahdlatul Ulama introduced the use of madhhab manhajī through istinbāṭ method in addition to madhhab qawlī. However, the co-existence of these two methods creates everlasting polarization within Nahdlatul Ulama. There once the division of application, though, in which manhajī was employed in mawḍū'īyah cases and qawlī was practised in wāqi‘īyah cases, but it did not last long. The National Congress of Nahdlatul Ulama in 2015, when istinbāṭ of madhhab manhajī was discussed once again, unveiled fierce debates between supporters of the two methods. The East Java Branch of Nahdlatul Ulama, which are fervent supporters of qawlī, insists on its sole employment in the fatwa. All their baḥth al-masā’il wāqi‘īyahs after the 2015 Congress use qawlī. However, manhajī start to appear in their baḥth al-masā’il mawḍū‘īyah, especially in cases where various approaches should be deployed, such as fatwa on Islam Nusantara.